Contrasting Farm Livelihoods in Climate Sensitive Agro-Ecosystems in Odisha - Usha Das; M. A. Ansari, Souvik Ghosh, A. K. Shukla, V. L. V Kameswari, Neelam Bhardwaj; G. S. Kushwaha (Indian Journal of Extension Education, 2022)
The spree of tackling climate change issues stems from every global corner, which remains unique to specific agro-ecosystems. Rural India with a fair majority of livelihoods dependent on agriculture, are facing the severity of challenges to cope up with climate change. Therefore, livelihood analysis is an important aspect to address the climate change issues. Present study was conducted in the year 2020-21, in a climatically vulnerable state of India, Odisha, which suffers from climate induced natural disasters both in coastal and non-coastal ecosystems. Sustainable livelihood framework was followed in analyzing differential level of human, social, physical, financial and social assets holding of three dominant livelihood groups, viz., crop, livestock and crop + livestock farmers in one each coastal and non-coastal districts covering a total of 200 farm households. The analyses showed contrasting livelihood status with varied level of assets, crop + livestock farmers having above average overall livelihood level and social assets being at above average level contributing highest to overall livelihood status. Overall level of coastal livelihoods was at lower level as compared to non-coastal livelihoods. Better livelihood assets along with both technological and institutional interventions result in better insulation to rural households against ill effects of climate change events.